Four new species of Fauveliopsidae (Annelida, Sedentaria) from the Gulf of Thailand - Plathong, Jintana; Plathong, Sakanan; Klangnurak, Wanlada; Salazar-Vallejo, Sergio I. (Zootaxa, 2026)
Four new species of Fauveliopsidae, Fauveliopsis pladang sp. nov., Laubieriopsis tantawan sp. nov., Riseriopsis chaba sp. nov., and R. plahmuk sp. nov., are described from the Gulf of Thailand from sediments at 50–80 m water depth. Fauveliopsis pladang sp. nov., can be distinguished from other species by having 41 chaetigers; anterior parapodia with two acicula chaetae per bundle; in median and posterior segments 1 aciculum and 1 capillary per bundle. Laubieriopsis tantawan sp. nov., differs from all other species in the genus by having 27–43 chaetigers, body annulate; 2 acicula per bundle in anterior parapodia; in median and posterior parapodia with 1 aciculum and 1 capillary per bundle. Riseriopsis chaba sp. nov., can be distinguished from other species by having 34 chaetigers; anterior parapodia with 2 acicula per bundle; median and posterior notopodia with one aciculum and one capillary per bundle; median neuropodia with 1 aciculum and 2 capillaries per bundle; posterior neuropodia with 1–2 acicula and 1 capillary per bundle. Riseriopsis plahmuk sp. nov., can be distinguished from other species by having 2–4 acicula per bundle along anterior segments; median segments with 1–2 acicula and 1–2 capillaries per bundle; and posterior parapodia with 1–6 acicula and 1–5 capillaries per bundle. Genetic data, sequencing of the cytochrome oxidase subunit I (COI) of L. tantawan sp. nov., and R. plahmuk sp. nov., are reported. Update keys for identifying species of Fauveliopsis, Laubieriopsis and Riseriopsis are also provided.